Bosporan Tumulus With Imprint Of Rhodian Coin - Vinogradov, Yurii (Acta Archaeologica Lodziensia, 2019)
In the Hellenistic period Rhodes was an important centre of trade and wine production. Finds of Rhodian amphorae stamps are very common in the Northern Black sea region, but Rhodian coins are quite rare. Some finds from the tumuli of the Cimmerian Bosporus demonstrate Rhodian influence also. One tumulus excavated on the Tuzla cape (the Taman peninsula) in 1885 is especially interesting. A rich grave dating to the end of the 3rd or beginning of the 2nd century BC was excavated. The grave inventory consists of two Greek vases, one gold wreath, a silver ladle (kyathos), a silver strainer of unusual form, and a silver footless bowl of mastos type, bearing a gold indication of a Rhodian coin. It is the only find of such type in the aristocratic burials of the Bosporan Kingdom.